Graphene mode-locked femtosecond laser at 2 μm wavelength - Ma, J. (2013)
We experimentally demonstrated a passively mode-locked femtosecond laser by using a graphene-based saturable absorber mirror (graphene SAM) in the spectral region of 2 μm. The graphene SAM was fabricated by transferring chemical-vapor-deposited, high-quality, and large-area graphene on a highly reflective plane mirror. Stable mode-locked laser pulses as short as 729 fs were obtained with a repetition rate of 98.7 MHz and an average output power of 60.2 mW at 2018 nm.